Analiza koszykowa jako klasyczny przykład wykorzystania reguł skojarzeniowych - Łapczyński, Mariusz (Market Basket Analysis as a Classical Implementation of Association Rules, 2006)
This article presents popular data mining tool - association rules. The author demonstrates common measures of quality i.e. support and confidence. He focuses on the main research area - market basket analysis and describes all types of rules (qualitative and quantitative, single-level and multilevel, single-dimensional and multi-dimensional). Furthermore, problems of minimum support and minimum confidence are mentioned. The article includes a list of several computer programmes - implementations of association rules.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1107, s. 523-527